2023
DOI: 10.1038/s41467-023-38568-5
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin toxicity is counteracted by the activation of the p38/ATF-7 signaling pathway in post-mitotic C. elegans

Abstract: Cisplatin kills proliferating cells via DNA damage but also has profound effects on post-mitotic cells in tumors, kidneys, and neurons. However, the effects of cisplatin on post-mitotic cells are still poorly understood. Among model systems, C. elegans adults are unique in having completely post-mitotic somatic tissues. The p38 MAPK pathway controls ROS detoxification via SKN-1/NRF and immune responses via ATF-7/ATF2. Here, we show that p38 MAPK pathway mutants are sensitive to cisplatin, but while cisplatin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…38,39 Specifically, the phosphorylation of SKN-1 is regulated upstream by the activation of components (SEK-1 and PMK-1) of the p38 MAPK pathway in reaction to increased ROS levels. 40 Furthermore, the antioxidant-promoting effects of IIS are reliant on HSF-1. 41 HSF-1 is suggested to work collaboratively with, yet distinctly from, DAF-16 to promote longevity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Specifically, the phosphorylation of SKN-1 is regulated upstream by the activation of components (SEK-1 and PMK-1) of the p38 MAPK pathway in reaction to increased ROS levels. 40 Furthermore, the antioxidant-promoting effects of IIS are reliant on HSF-1. 41 HSF-1 is suggested to work collaboratively with, yet distinctly from, DAF-16 to promote longevity.…”
Section: Discussionmentioning
confidence: 99%
“…52 Previous studies on C. elegans have shown that SKN-1, activated by sek-1 , nsy-1 and pmk-1 , could synthesize ROS-resistant detoxifying enzymes, thereby assisting in the regulation of DAF-16. 40 Through the lifespan experiments with the 12 mutants, we reported that EGCG did not increase the lifespan of daf-16 , skn-1 , eat-2 , sir-2.1 , hsf-1 , age-1 , jnk-1 , jkk-1 , pmk-1 , sek-1 , aak-2 , and nsy-1 mutants, confirming that the beneficial effects from EGCG were associated with the IIS and MAPK pathways (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%